PERSEPSI MASYARAKAT DESA SEKITAR HUTAN TERHADAP TAHURA SULTAN ADAM DAN KHDTK DIKLAT ULM - Patar Perdinand Ariokta; Hafiziannor Hafiziannor; Eva Prihatiningtyas (Universitas Lambung Mangkurat, 2020)
The study aims to analyse public perceptions of the Sultan Adams Tahura and the Lambung Mangkurat University Research Forest (KHDTK ULM) existence in the Karang Intan sub-district of Banjar Regency. The research site is located in East Mandiangin Village, Mandiangin West Village and Kiram village, Karang Intan District, Banjar Regency. The research using descriptive methods with the questionnaire and the modification formula Levis, 2013 applied to analyse data. The result of this study indicated that the tribes who live surrounds the Sultan Adam Tahura and KHDTK ULM are Banjar tribe who work as farmers. The perceptions of the Mandiangin Barat community to Tahura Sultan Adam, is getting the highest score with an average score of 8.4, following Mandiangin Timur with an average score of 8 and Kiram wich scored 7.8; while the highest perception score to KHDTK ULM was found in the Mandiangin Timur Village an average score of 11.6, followed by the Mandiangin Barat scored 10, and Kiram scored 9.2. Overall perceptions are ranged from MEDIUM to GOOD category.Keywords: People’s perception, Tahura Sultan Adam, KHDTK ULM